Controle de qualidade, análise fitoquímica e atividade antimicrobiana de Bidens pilosa Linnaeus (Asteraceae) - Santos, Daniele Damian dos (2015)
The use of natural resources as a treatment and cure of diseases is an old and still widely used method. The study aims to determine the antimicrobial activity and secondary metabolites from plants Bidens pilosa L. obtained in different crops as well as perform the physical-chemical quality control of plant drug. Studying the in vitro germination were tested different conditions and diasporas storage periods, and the ex vitro different substrate preparation. In micropropagation, they were used apical segments and nodal, and combinations of BAP and NAA. The conditions and diasporas storage period influenced the germination, with the highest percentage of germination when kept at 25°C for 30 days (60.4%), and for 120 days at 10°C (75%). With cultivation in greenhouse there was no difference in the percentage of germination among different substrate preparation (76% and 70% not autoclaved autoclaved). In micropropagation, the absence of growth regulators gave the highest percentage of shoots (37.5% apical segment and 10% nodal segment). From the plants obtained from different crops, traditional (TC), greenhouse (GC), in vitro germination (IG) and micropropagation in vitro (IM), extracts and fractions were performed, evaluating the antimicrobial activity. The best antibacterial activity was obtained with the butanol fraction (TC), with S. epidermidis (MIC-16 μg/mL) and the best antifungal activity was obtained with hexane fraction (GC) and chloroform (TC) with S. cerevisiae (MIC-16 μg/mL). The analysis identified by HPLC-DAD chlorogenic acid, caffeic acid and rutin. Where the greatest chlorogenic acid contents were to extract and acetate fraction of the greenhouse (22.92 and 10.32 mg/g, respectively) and butanol fraction of traditional cultivation (21.71 mg/g); the highest rutin content were found to extract, acetate and butanol fraction of traditional farming (46.39, 229.81 and 23.16 mg/g, respectively). The quality control parameters established for the plant material, allows the use of B. pilosa with quality and safety. The different cultures of B. pilosa provided a variation in production of secondary metabolites and the identified compounds can be attributed to antimicrobial activity on plant species.